Synthesis of New 3-Arylcoumarins Bearing N-Benzyl Triazole Moiety: Dual Lipoxygenase and Butyrylcholinesterase Inhibitors With Anti-Amyloid Aggregation and Neuroprotective Properties Against Alzheimer’s Disease - Pourabdi, Ladan; Küçükkılınç, Tuba Tüylü; Khoshtale, Fatemeh; Ayazgök, Beyza; Nadri, Hamid; Farokhi Alashti, Farid; Forootanfar, Hamid; Akbari, Tayebeh; Shafiei, Mohammad; Foroumadi, Alireza; Sharifzadeh, Mohammad; Shafiee Ardestani, Mehdi; et al. (Frontiers in Chemistry, 2022)
A novel series of coumarin derivatives linked to the N-benzyl triazole group were synthesized and evaluated against 15-lipoxygenase (15-LOX), and acetyl- and butyrylcholinesterase (AChE and BuChE) to find the most potent derivative against Alzheimer’s disease (AD). Most of the compounds showed weak to moderate activity against ChEs. Among the most active BuChE and 15-LOX inhibitors, 8l and 8n exhibited an excellent neuroprotective effect, higher than the standard drug (quercetin) on the PC12 cell model injured by H2O2 and significantly reduced aggregation of amyloid Aβ1-42, with potencies of 1.44 and 1.79 times higher than donepezil, respectively. Compound 8l also showed more activity than butylated hydroxytoluene (BHT) as the reference antioxidant agent in reducing the levels of H2O2 activated by amyloid β in BV2 microglial cells. Kinetic and ligand–enzyme docking studies were also performed for better understanding of the mode of interaction between the best BuChE inhibitor and the enzyme. Considering the acceptable BuChE and 15-LOX inhibition activities as well as significant neuroprotection, and anti-amyloid aggregation activities, 8l and 8n could be considered as potential MTDLs for further modification and studies against AD.